Numbers of Calling Whales in the North Pacific - Watkins, William A.; Daher, Mary Ann; George, Joseph E. (2001)
Since November 1995, the U.S. Navy's Sound Surveillance System (SOSUS) and other hydrophone arrays were used to regularly sample the occurrence of whale sounds in four regions bordering the continental margins across the North Pacific. The numbers of whales heard calling varied with season and location for each species, blue whales (Balaenoptera musculus), fin whales (Balaenoptera physalus), and humpback whales (Megaptera novaeangliae). For blue whales, calling during the fall season averaged 5 whales per event, winter averaged 1.5 whales per event, spring averaged 1 whale, and summer averaged 1.5 whales. For fin whales the numbers of whales heard ('F' calls from individuals) during winter averaged 3 whales per event, spring and fall calling averaged 1.5 whales, and summer averaged 1 whale. The 'J' calling events, regardless of season, were judged to be from at least 6 fin whales. Humpback singing typically was from 3 whales. These number demonstrated seasonal variations in calling whales for each region.